2019
DOI: 10.1136/bmjdrc-2018-000577
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and its associated factors among adult patients with type II diabetes attending Mizan Tepi University Teaching Hospital, Southwest Ethiopia

Abstract: BackgroundHealth-related quality of life (HRQOL) has become an important measure for evaluating patient treatment with non-curable chronic disease. The aim of the study was to assess HRQOL and its associated factors among patients with type II diabetes.MethodsThis is an institution-based, cross-sectional study conducted from March 13 to May 9, 2018. A total of 267 patients with type II diabetes who visited the clinic for follow-up for at least 3 months and who were 18 years or older were included in the study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
64
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(92 citation statements)
references
References 19 publications
(34 reference statements)
21
64
2
5
Order By: Relevance
“…Our finding demonstrated that, among domains of HRQoL, the physical health was the most affected domain in diabetic group and this is of course in agreement with other reports [14,16,31]. This consistency could be defensible by diabetes has more physical than mental (psychological) manifestations [32].…”
Section: Comparison Of Hrqol Among Adults With Andwithout Dmsupporting
confidence: 92%
See 3 more Smart Citations
“…Our finding demonstrated that, among domains of HRQoL, the physical health was the most affected domain in diabetic group and this is of course in agreement with other reports [14,16,31]. This consistency could be defensible by diabetes has more physical than mental (psychological) manifestations [32].…”
Section: Comparison Of Hrqol Among Adults With Andwithout Dmsupporting
confidence: 92%
“…The current study shows that an older age was associated with poor environmental health in diabetic group. This finding is lined with previous studies conducted in different research setting [9,12,16,33,34]. Such outcome may indicate that younger people are more likely to adore better health than elder and this may not surprising because as age increase the physiological function decline and prevent different activity of the body which might impair HRQOL .…”
Section: Factor Associated With Hrqol In Diabetic Patientssupporting
confidence: 90%
See 2 more Smart Citations
“…This finding contradict with several previous studies. [16][17][18] The previous studies found relationships between several factors such as comorbidities and low incomes and low utility score. 16 After factors were controlled using multiple logistic regression only two factors were seen to be associated with HbA 1C control; an education level higher than secondary school and treatment with insulin therapy.…”
Section: Factors Associated With Utilitymentioning
confidence: 99%